Intra-arterial tenecteplase is safe and may improve the first-pass recanalization for acute ischemic stroke with large-artery atherosclerosis: the BRETIS-TNK trial - Zhao, Zi-Ai; Qiu, Jing; Wang, Lu; Zhao, Yong-Gang; Sun, Xian-Hui; Li, Wei; Liu, Xin; Li, Xiao-Long; Liu, Liang; Chen, Ming-Rui; Chen, Hui-Sheng (Frontiers in Neurology, 2023)
Background and purpose: The first-pass recanalization of endovascular treatment (EVT) is closely correlated with clinical outcome of patients with large vessel occlusion (LVO) stroke. The aim of the study was to explore whether intra-arterial tenecteplase (TNK) during the first pass of EVT can increase first-pass successful reperfusion and improve the neurological outcome in AIS-LVO patients. Materials and Methods: The BRETIS-TNK trial (NCT 04202458) was a prospective, single-arm, single center study. Twenty-six eligible AIS-LVO patients with large-artery atherosclerosis etiology were consecutively enrolled from December 2019 to November 2021. Intra-arterial TNK (4 mg) after microcatheter navigation through the clot was administered, followed by TNK (0.4 mg/min) given continuously for 20 minutes after the first retrieval attempt of EVT without confirmation of the reperfusion status by DSA. The 50 control patients comprised of a historical cohort before the BRETIS-TNK trial (from March 2015 to November 2019). Successful reperfusion was defined as modified Thrombolysis In Cerebral Infarction (mTICI) ≥2b. Results: The first-pass successful reperfusion rate was higher in the BRETIS-TNK vs control group (53.8% vs 36%, p=0.14), and the difference became statistically significant after propensity score matching (53.8% vs 23.1%, p=0.03). There was no difference in symptomatic intracranial hemorrhage between the BRETIS-TNK and control groups (7.7% vs 10.0%, p=0.92). There was a trend toward higher proportion of functional independence at 90 days in the BRETIS-TNK comparing with the control group (50% vs. 32%, p=0.11). Conclusions: This is the first study to report that intra-arterial TNK during the first pass of EVT seems safe and feasible in AIS-LVO patients.